Obesidad en la diabetes mellitus: un gran peligro para el corazón y la vida - Vega Candelario, Rodolfo; Vega Yero, Iris O.; Vega Jiménez, Junior; Milián Moreira, Sarai (CorSalud, 2021)
Obesidad en la diabetes mellitus: un gran peligro para el corazón y la vida